Barriers to provider-initiated testing and counselling for children in a high HIV prevalence setting: a mixed methods study. - Katharina Kranzer; Jamilah Meghji; Tsitsi Bandason; Ethel Dauya; Stanley Mungofa; Joanna Busza; Karin Hatzold; Khameer Kidia; Hilda Mujuru; Rashida A Ferrand (PLoS Medicine, 2014)
There is a substantial burden of HIV infection among older children in sub-Saharan Africa, the majority of whom are diagnosed after presentation with advanced disease. We investigated the provision and uptake of provider-initiated HIV testing and counselling (PITC) among children in primary health care facilities, and explored health care worker (HCW) perspectives on providing HIV testing to children.Children aged 6 to 15 y attending six primary care clinics in Harare, Zimbabwe, were offered PITC, with guardian consent and child assent. The reasons why testing did not occur in eligible children were recorded, and factors associated with HCWs offering and children/guardians refusing HIV testing were investigated using multivariable logistic regression. Semi-structured interviews were conducted with clinic nurses and counsellors to explore these factors. Among 2,831 eligible children, 2,151 (76%) were offered PITC, of whom 1,534 (54.2%) consented to HIV testing. The main reasons HCWs gave for not offering PITC were the perceived unsuitability of the accompanying guardian to provide consent for HIV testing on behalf of the child and lack of availability of staff or HIV testing kits. Children who were asymptomatic, older, or attending with a male or a younger guardian had significantly lower odds of being offered HIV testing. Male guardians were less likely to consent to their child being tested. 82 (5.3%) children tested HIV-positive, with 95% linking to care. Of the 940 guardians who tested with the child, 186 (19.8%) were HIV-positive.The HIV prevalence among children tested was high, highlighting the need for PITC. For PITC to be successfully implemented, clear legislation about consent and guardianship needs to be developed, and structural issues addressed. HCWs require training on counselling children and guardians, particularly male guardians, who are less likely to engage with health care services. Increased awareness of the risk of HIV infection in asymptomatic older children is needed.